A Semiotic Analysis of a Texas Cooperative Extension Marketing Packet - Leslie Edgar; Tracy Rutherford (Journal of Applied Communications, 2012)
Semiotic analysis in agricultural communications / education and related fields is largely unexplored territory. This study used semiotics, a theory of the production and interpretation of meaning based on images, to evaluate a Texas Cooperative Extension marketing packet. Photographic and logo images throughout the packet were analyzed by employing descriptive methodology and quantitative content analysis methods to “identify the symbols used in the image and determine their meaning for society as a whole”. The purpose of the study was to interpret the messages directed to the audience and determine if they matched the perceived meanings. The findings revealed five repeating themes within the 81 images included in the marketing packet. The themes were: messages portrayed, diversity, relationships, exchange of information, and stereotypes. Each image was analyzed for denotative and connotative meaning. Results showed the images portrayed predominately positive messages while logos were neutral. Adult Caucasian females were depicted as the primary age, ethnic, and gender group. The most reoccurring relationships depicted were that of families and a student / mentor relationship. For information exchange, more images portrayed hands-on learning than dialogue instruction. Findings also indicate visual stereotypes were present. Additionally, no messages regarding individuals with disabilities were discovered. This research focused solely on visual analyses, further research is recommended to evaluate Extension’s marketing tactics both visually and in print to determine if marketing materials are meeting the needs of the organization and their publics. Additional visual marketing assessments should continue.
Keywords: visual communications; semiotics; Texas Cooperative Extension; marketing; visual literacy